Leadership equation : leadership, management and the Myers-Briggs - Barr, Lee (Eakin P. AustinUS, 1989)
Seeks to present the foundation for building interperaonal skills that leaders require, using the dimensions, categories, and types identified by the Myers-Briggs Type Indicator. Examines topics including: communication, information; judgement, organizational and managerial style; and control. Uses case studies throughout to illustrate concepts including: the need for balancing; failure to balance preferences; thinker-feeler development.